2009
DOI: 10.1182/blood-2008-07-166421
|View full text |Cite
|
Sign up to set email alerts
|

TERC and TERT gene mutations in patients with bone marrow failure and the significance of telomere length measurements

Abstract: Dyskeratosis congenita (DC) is a rare inherited form of bone marrow failure (BMF) caused by mutations in telomere maintaining genes including TERC and TERT. Here we studied the prevalence of TERC and TERT gene mutations and of telomere shortening in an unselected population of patients with BMF at our medical center and in a selected group of patients referred from outside institutions. Less than 5% of patients with BMF had pathogenic mutations in TERC or TERT. In patients with BMF, pathogenic TERC or TERT gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 44 publications
4
130
0
3
Order By: Relevance
“…Finally, mutations of the regulator of telomere elongation helicase 1 (RTEL1 gene) have been identified in patients with severe autosomal recessive DC [35] (Table 1). DC is a rare inherited disorder characterized by a typical triad of clinical manifestations: skin hyperpigmentation, oral leukoplakia and nail dystrophy [26]. The majority of cases (>80 %) occur in children and are diagnosed usually about the age of ten when the children start presenting bone marrow failure together with the previously described clinical triad.…”
Section: Telomerase In Degenerative Diseasesmentioning
confidence: 99%
“…Finally, mutations of the regulator of telomere elongation helicase 1 (RTEL1 gene) have been identified in patients with severe autosomal recessive DC [35] (Table 1). DC is a rare inherited disorder characterized by a typical triad of clinical manifestations: skin hyperpigmentation, oral leukoplakia and nail dystrophy [26]. The majority of cases (>80 %) occur in children and are diagnosed usually about the age of ten when the children start presenting bone marrow failure together with the previously described clinical triad.…”
Section: Telomerase In Degenerative Diseasesmentioning
confidence: 99%
“…La mesure de la longueur des télomères dans les cellules du sang périphérique constitue à ce jour le test de dépistage de référence pour l'identification des patients atteints de DC du fait de la relation communément admise entre DC/aplasie médullaire et télomères anormalement courts [24]. Cette mesure peut s'effectuer par Southern blot, PCR (polymerase chain reaction) quantitative ou FISH (fluorescence in situ hybridization) quantitatif parfois couplé à la cytométrie de flux (flow-FISH) [24][25][26].…”
Section: Longueur Des Télomères Et Diagnostic De DCunclassified
“…Cette mesure peut s'effectuer par Southern blot, PCR (polymerase chain reaction) quantitative ou FISH (fluorescence in situ hybridization) quantitatif parfois couplé à la cytométrie de flux (flow-FISH) [24][25][26]. La longueur des télomères des leucocytes diminuant avec l'âge chez les individus sains, ce test diagnostic se révèle plus discriminant chez les enfants que chez les adultes [26].…”
Section: Longueur Des Télomères Et Diagnostic De DCunclassified
See 1 more Smart Citation
“…Another group recently concluded that telomere length was sensitive but not specific in screening for DC [38]. The flow-FISH method used to determine telomere length differed from previously established methods in several ways [3;39;40].…”
Section: Making the Diagnosismentioning
confidence: 99%